Ethanol extract of asiasari radix preferentially induces apoptosis in G361 human melanoma cells by differential regulation of p53 - Kwang-Ha Park; Jeong-Hae Choi; Yeon-Suk Song; Gyoo-Cheon Kim; Jin-Woo Hong (BMC, 2019)
Abstract Background In Korea and China, asiasari radix (AR) is widely used as a traditional anti-inflammatory and analgesic agent. After its skin-regenerating and hair loss-preventing activities were identified, several types of AR extracts were used for aesthetic purposes. Nevertheless, the effect of ARE on various types of skin cancers was not fully studied yet. Methods In this study, we tested the effect of an ethanolic AR extract (ARE) on G361 human melanoma and HaCaT human keratinocyte cell lines. After ARE exposure, cell growth and the expression patterns of proteins and genes were monitored. Results The ARE-mediated cell growth inhibition was greater in G361 cells than in HaCaT cells due to differences in its cell growth regulation effects. Interestingly, ARE treatment induced caspase-3-mediated apoptosis in G361 cells, but not in HaCaT cells. Furthermore, ARE reduced the expression of p53 and p21 proteins in G361 cells, whereas it induced their expression in HaCaT cells. ARE induced cell death in G361 cells through the reactive oxygen species (ROS)-dependent regulation of p53 and p21 in G361 cells. Microarray analysis showed that ARE regulates Mouse double minute 2 homolog (MDM2) and CASP8 and FADD-like apoptosis regulator (CFLAR) gene expression in G361 and HaCaT cells differently. Conclusion The treatment of ARE preferentially induces apoptosis in melanoma cells by the ROS-dependent differential regulation of p53 level. Therefore, ARE can be used as a new medicinal option for melanoma.